PENGARUH PARTISIPASI KELOMPOK WANITA TANI MENTARI TERHADAP KESEJAHTERAAN KELUARGA DI KALURAHAN MAGUWOHARJO KABUPATEN SLEMAN - Damai Vianti; Artita Devi Maharani; Eska Stefani (JURNAL ILMIAH AGRITAS, 2024)
This study aims to determine and analyze the level of participation of KWT Mentari on family welfare covering urban agricultural businesses that utilize yard land and local food management with assistance from CSR BRI cares that support women's empowerment through KWT in Kalurahan Maguwoharjo, Sleman Regency. This research is a quantitative research that focuses on KWT Mentari in Kalurahan Maguwoharjo, Sleman Regency. The number of respondents to this study was 35 people who were determined by census method. The results of research in the field of participation of KWT Mentari members are high, starting from planning participation obtained a value of 85%, implementation 85%, utilization of results 83% and evaluation 86%. In the results of the study, the level of family welfare of KWT Mentari members was high at the level of Pre-Prosperous Families (PPP) known to 0 respondents, Prosperous Family I (KS I) known to 3 respondents, Prosperous Family II (KS II) known to 10 respondents, Prosperous Family III (KS III) known to 14 respondents and Prosperous Family III + known to 8 respondents. In the statistical test results, the results of the T test were obtained from the participation variable, the calculated T value was 5.856 > T table 2.035, meaning that the participation variable had a significant effect on family welfare. In the results of the Coefficient of Determination test, an R square value of 51.0% was obtained, which contains the understanding that participation affects family welfare by 51.0%, while the remaining 49.0% is influenced by other factors.